PENGARUH PSYCHOLOGICAL CAPITAL DAN BEBAN KERJA TERHADAP KINERJA KELOMPOK PENYELENGGARA PEMUNGUTAN SUARA PADA PEMILIHAN UMUM SERENTAK TAHUN 2024 DI KECAMATAN REJOSO KABUPATEN PASURUAN - Kamil, Febrina Nur Halizah; Hastari, Sri; Ghifary, MT. (Yayasan Education and Social Center, 2024)
KPPS is the lowest level election organizer to carry out voting at TPS. This study was motivated by the findings made by KPPS in making mistakes in writing C-Results or C-Result copies and incorrectly inserting C-Results into the ballot box so that the ballot box was opened during the plenary session at the PPK level. This study aims to determine the effect of psychological capital and workload on KPPS performance. This study uses a quantitative approach with primary data as a data source obtained from the results of the questionnaire. The population is 931 KPPS using the slovin technique taken based on the proportional sampling technique with a sample size of 100 respondents. This study uses instrument testing, descriptive analysis, classical assumption testing, multiple linear analysis, determinant coefficient analysis, and hypothesis testing. The results of this study indicate that (1) psychological capital and workload simultaneously influence the performance of KPPS, it is concluded that the better the psychological capital and workload of KPPS, the better the performance of KPPS (2) psychological capital partially influences the performance of KPPS, if the psychological capital of KPPS is high, it can improve the performance of KPPS, this is because a person's psychological capital can encourage better performance (3) workload partially influences the performance of KPPS if the workload is good, the performance of KPPS will improve